2008
DOI: 10.1007/s10791-008-9044-1
|View full text |Cite
|
Sign up to set email alerts
|

Document keyphrases as subject metadata: incorporating document key concepts in search results

Abstract: Most search engines display some document metadata, such as title, snippet and URL, in conjunction with the returned hits to aid users in determining documents. However, metadata is usually fragmented pieces of information that, even when combined, does not provide an overview of a returned document. In this paper, we propose a mechanism of enriching metadata of the returned results by incorporating automatically extracted document keyphrases with each returned hit. We hypothesize that keyphrases of a document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…This is because despite the large overlap between MA and VK, there is not overlap between MA and HA 1 . Whereas when additional gold standards, HA 2 and HA 3 , are available and used for evaluating the overall inter-indexer consistency score of the machine annotator, a more accurate estimation of the machine annotator's performance could be achieved. In fact, as can be seen in the illustration, if the quality of MA and HA 1 were to be compared with each other by using HA 2 and HA 3 as gold standards, the overall quality of MA would be significantly higher than HA 1 Whereas, in case of the former, additional sets of keyphrases are usually not available and need to be created manually, for example the small wiki-20 dataset used in this work has taken ninety man-hours to create.…”
Section: Experimental Results and Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because despite the large overlap between MA and VK, there is not overlap between MA and HA 1 . Whereas when additional gold standards, HA 2 and HA 3 , are available and used for evaluating the overall inter-indexer consistency score of the machine annotator, a more accurate estimation of the machine annotator's performance could be achieved. In fact, as can be seen in the illustration, if the quality of MA and HA 1 were to be compared with each other by using HA 2 and HA 3 as gold standards, the overall quality of MA would be significantly higher than HA 1 Whereas, in case of the former, additional sets of keyphrases are usually not available and need to be created manually, for example the small wiki-20 dataset used in this work has taken ninety man-hours to create.…”
Section: Experimental Results and Evaluationmentioning
confidence: 99%
“…Annotating scientific documents with keyphrases as subject/topical metadata helps both humans and information retrieval systems to focus their search and discovery efforts on the most relevant items of interest and reduces the recall effort (i.e., ratio of desired to examined) [2,3]. However, despite the fact that authors of scientific literature, especially those published in journals and conference proceedings, are encouraged and often required by editors to provide a list of keyphrases, scientific documents with manually assigned keyphrases by either authors or professional annotators are still in the minority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We treat the noun phrases in the document as the candidate keyphrases [1]. To identify the noun phrases, documents should be tagged.…”
Section: Noun Phrase Identificationmentioning
confidence: 99%
“…A number of previous works has suggested that document keyphrases can be useful in a various applications such as retrieval engines [1], [2], [3], browsing interfaces [4], thesaurus construction [5], and document classification and clustering [6].…”
Section: Introductionmentioning
confidence: 99%